Answer:
![d = (9t^(2) )/(2) - (2)/(9) t + (t^3)/(3)](https://img.qammunity.org/2021/formulas/mathematics/college/zma6fxffx8kihxf9yq7hnwpr4oeuxpl2o7.png)
Explanation:
Given the equation of velocity w.r.to time 't':
![v=9t-(2)/(9)+t^2 ...... (1)](https://img.qammunity.org/2021/formulas/mathematics/college/ngdjhp2qwk709mhls5rxd0545uywoxxo6y.png)
Formula for Displacement:
![Displacement = \text{velocity} * \text{time}](https://img.qammunity.org/2021/formulas/mathematics/college/btankx0zbgn5p105tapa3i9kgxutnjzl8e.png)
So, if we find integral of velocity w.r.to time, we will get displacement.
![\Rightarrow \text{Displacement}=\int {v} \, dt](https://img.qammunity.org/2021/formulas/mathematics/college/a0zz1ju688kf1enz885y3h1lhb0n9q09kr.png)
![\Rightarrow \int {v} \, dt = \int ({9t-(2)/(9)+t^2}) \, dt \\\Rightarrow \int{9t} \, dt - \int{(2)/(9)} \, dt + \int{t^2} \, dt\\\Rightarrow s=(9t^(2) )/(2) - (2)/(9) t + (t^3)/(3) + C ....... (1)](https://img.qammunity.org/2021/formulas/mathematics/college/r8vuiuk5gsb0bdylkfbzxi2spkx7zjtmgw.png)
Here, C is constant (because it is indefinite integral)
Formula for integration used:
![1.\ \int({A+B}) \, dx = \int {A} \, dx + \int{B} \, dx \\2.\ \int({A-B}) \, dx = \int {A} \, dx - \int{B} \, dx \\3.\ \int{x^(n) } \, dx = (x^(n+1))/(n+1)\\4.\ \int{C } \, dx = Cx\ \{\text{C is a constant}\}](https://img.qammunity.org/2021/formulas/mathematics/college/1jrsjsbodi06t8m53fc677edw83xeehj27.png)
Now, it is given that s = 0, when t = 0.
Putting the values in equation (1):
![0=(9* 0^(2) )/(2) - (2)/(9)* 0 + (0^3)/(3) + C\\\Rightarrow C = 0](https://img.qammunity.org/2021/formulas/mathematics/college/u43sm90f2b63k0t46ro0crykjcazgntctp.png)
So, the equation for displacement becomes:
![s=(9t^(2) )/(2) - (2)/(9) t + (t^3)/(3)](https://img.qammunity.org/2021/formulas/mathematics/college/9gc7xok82ap4g9zhefyzrfo25eurngeebs.png)